Development of High Resolution Melting Analysis as a Diagnostic Tool for Molecular Detection of Toxoplasma Infection in Pregnant Women and HIV Positive Cases - Ahmad HOSSEINI-SAFA; Saeedeh SHOJAEE; Seyed Alireza SALAMI; Mehdi MOHEBALI; Sedigheh HANTOUSHZADEH; Parisa MOUSAVI; Seyed Ali DEHGHAN MANSHADI; Hosein KESHAVARZ VALIAN (Tehran University of Medical Sciences, 2020)
Background: Toxoplasma gondii is an obligate intracellular protozoan with worldwide distribution. Diagnosis of toxoplasmosis is a very critical issue, especially in pregnant women and immunocompromised patients. The aim of this study was rapid detection of T. gondii DNA in peripheral blood samples (PBS) employing HRM technique and using RE gene. Methods: Totally, 242 samples from pregnant women and human immunodeficiency virus (HIV) patients were collected from different hospitals and medical centers of Tehran during Oct 2017 to Dec 2018. High resolution melting analysis (HRM) using partial sequences of repetitive element (RE) gene was done and compared with ELISA test. Results: Overall, 51 were positive for acute toxoplasmosis that among them, 12 and 20 reported as positive in pregnant women and HIV+ patients, respectively using HRM technique. Among 70 patients in chronic phase of disease, 10 and 3 samples were reported as positive for pregnant women and HIV+ patients respectively. From 121 negative control, 3 (4.62%) samples associated with HIV+ patients, showed positive real-time PCR and HRM analysis results. Conclusion: For the first time, HRM technique via employing RE gene was used for detection of T. gondii infection in PBS. This method is suitable, helpful and in parallel with serological methods for early diagnosis of acute as well as active form of toxoplasmosis in pregnant women and HIV+ patients. The use of techniques based on melt curve and through employing next-generation dyes for diagnosis of T. gondii would be accessible for patients in developing countries.